Analysis of mortality trends in children aged 0–14 in Brazil and the northeast macroregion: a time series study (2000–2019) - Diniz Alves, Robenilson; da Silva Ramos Marinho, Cristiane; da Costa Cantas Santiago, Janmilli; Tavares Pinheiro, Yago; De Goes Bay Junior, Osvaldo; Galante Sousa, Klayton (Frontiers in Pediatrics, 2025)
IntroductionChild deaths in Brazil have fallen significantly in recent decades. However, mortality rates remain high compared to countries with a Human Development Index considered very high. In addition, social problems and inequalities remain evident and require the promotion of effective public policies. However, since the beginning of the millennium, a governmental effort in favor of children's health has been underway, with actions that have contributed to improving mortality rates. In this context, it is essential to investigate the transformations of the first two decades of the 21st century.MethodsThis study aims to describe and identify the temporal trends in mortality rates for children aged 0–14 in Brazil and its macro-regions. This is an ecological, time-series study with a quantitative approach, based on secondary data on infant mortality (<1 year), childhood mortality (<5 years), and mortality in children between 5 and 14 years, in Brazil and in the Northeast Macroregion, between 2000 and 2019. Data was collected from January to August 2024 through the Mortality, Live Births, and Resident Population Information Systems provided by the Brazilian Institute of Geography and Statistics (IBGE). Trends were analyzed using Joinpoint statistical software.ResultsIn Brazil and the Northeast, there was a significant downward trend in infant and childhood mortality rates until 2014, after which the curve remained stationary. Among children aged 5–14, a continuous downward trend was observed, with regional and temporal variations, particularly a greater decrease after 2013 in the country and in 2012 in the Northeast. Black children had a higher percentage of deaths, males were more prevalent, and perinatal conditions were the main cause of death among children under 1 and 5 years old. External causes of morbidity and mortality prevailed as the main causes of death among children aged 5–14.DiscussionDuring the two decades studied, there was a significant reduction in mortality. However, the stagnation of rates since 2014 and the uneven profile of deaths indicate that social indicators and health actions were impacted by austerity measures, posing a challenge for the country in terms of maintaining, regionalizing, and strengthening effective public policies.